2015 International Conference on Fuzzy Theory and Its Applications (iFUZZY) 2015
DOI: 10.1109/ifuzzy.2015.7391894
|View full text |Cite
|
Sign up to set email alerts
|

Speed control design for a vehicle system using fuzzy logic and PID controller

Abstract: This paper consists of designing fuzzy and PID controllers for controlling the vehicle speed. The dynamic of the system is modeled to provide a transfer function for the plant. Fuzzy and PID controller are designed for linear model. The external disturbances such road grade is considered to stabilizing the system. Both controllers are modeled using MATLAB Simulink software. Finally, a comparative assessment of each simulated result is done based on the response characteristics

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 9 publications
0
7
1
Order By: Relevance
“…Before carrying out the hardware/software design of the proposed fuzzy controller, we have tested it by applying a car plant [26] according to our car dimensions, shown in Figure 5. It is a discrete transfer function given in (4).…”
Section: System Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Before carrying out the hardware/software design of the proposed fuzzy controller, we have tested it by applying a car plant [26] according to our car dimensions, shown in Figure 5. It is a discrete transfer function given in (4).…”
Section: System Modelmentioning
confidence: 99%
“…π›₯𝑣 π›₯𝑒 = 0.0007198z 2 +0.00217z+0.0003955 𝑧 3 -2.18z+1.487z-0.3009 (4) where u  is the control signal that is considered as throttle control and used to increase or decrease the engine driver force [26] and v  is the car speed in cm/s. Figure 4 presents the system model developed in MATLAB/Simulink environment.…”
Section: 𝐻(𝑧) =mentioning
confidence: 99%
“…Obtaining an admissible mathematical model is viable for a simple system, but this is not always possible for complex cases. To bridge this gap, non-model based control-strategies like neural and fuzzy techniques were later developed [5] and implemented in a number of control applications like, cruise control [6][7][8][9], industrial processes [10][11][12], robotics [13][14] and ball and beam/plate systems [15][16][17][18][19], etc.…”
Section: Introductionmentioning
confidence: 99%
“…The results showed improved performance with the neuro-fuzzy controller (Adaptive Neuro-Fuzzy Inference System, ANFIS) compared with manually tuned control (typically used in the industries). Munyaneza et al [7] concluded that PD control produces small rise time (in cruise-control system), yet it creates a high percentage of overshoot, resulting in overall poor performance as compared with fuzzy control. Similarly, Dawood et al [6] have compared PID, fuzzy logic, and genetic-algorithm for the cruise control application.…”
Section: Introductionmentioning
confidence: 99%
“…Many kinds of research concentrated on speed track. Proportional-integral-derivative (PID) based controller is applied in [12] which can realize speed tracking. To further improve the response speed, linear quadratic regulator (LQR) is also studied in [13].…”
Section: Introductionmentioning
confidence: 99%